Different Suture Materials for Arthroscopic Transtibial Pull-out Repair of Medial Meniscal Posterior Root Tears: A Human Biomechanical Study. Issue 9 (30th September 2019) - Nakama, Gilberto Y.; Aman, Zachary S.; Storaci, Hunter W.; Kuczmarski, Alexander S.; Krob, Joseph J.; Strauss, Marc J.
Background: Transtibial pull-out repair of the medial meniscal posterior root (MMPR) has been largely assessed through biomechanical studies. Biomechanically comparing different suture types would further optimize MMPR fixation and affect clinical care. Purpose/Hypothesis: The purpose of this study was to determine the optimal suture material for MMPR fixation. It was hypothesized that ultra high–molecular weight polyethylene (UHMWPE) suture tape would be biomechanically superior to UHMWPE suture and standard suture. Study Design: Controlled laboratory study. Methods: The MMPR attachment was divided in 24 human cadaveric knees and randomly assigned to 3 repair groups: UHMWPE suture tape, UHMWPE suture, and standard suture. Specimens were dissected down to the medial meniscus, and the posterior root attachments were sectioned off the tibia. Two-tunnel transtibial pull-out repair with 2 sutures, as determined by the testing group, was performed. The repair constructs were cyclically loaded between 10 and 30 N at 0.5 Hz for 1000 cycles to mimic the forces experienced on the medial meniscus during postoperative rehabilitation. Displacement was recorded at 1, 50, 100, 500, and 1000 cycles. Ultimate failure load, displacement at failure, and load at 3 mm of displacement (clinical failure) were also recorded. Results: UHMWPE suture tape had significantly less displacement of the medial meniscus when compared with standard suture at 1 (–0.22 mm [95% CI, –0.41 to –0.02]; P = .025) and 50 (–0.35 mm [95% CI, –0.67 to –0.03]; P = .029) cycles. There were no other significant differences observed in displacement between groups at any number of cycles. UHMWPE suture tape had significantly less displacement at the time of failure than standard suture (–3.71 mm [95% CI, –7.17 to –0.24]; P = .034). UHMWPE suture tape had a significantly higher load to reach the clinical failure displacement of 3 mm than UHMWPE suture (15.64 N [95% CI, 0.02 to 31.26]; P = .05). There were no significant differences in ultimate failure load between groups. Conclusion: The meniscal root repair construct with UHMWPE suture tape may be stronger and less prone to displacement than that with standard suture or UHMWPE suture. Clinical Relevance: UHMWPE suture tape may provide better clinical results compared with UHMWPE suture and standard suture.